Prospective trials of minor surgical procedures and high-fibre diet for haemorrhoids. - Keighley, M R (1979)
Two hundred and sixteen consecutive patients seen for the first time with symptomatic haemorrhoids entered trials of conservative and minor surgical treatment. They were divided into two groups according to their pretreatment maximal anal pressure. Patients with pressures of 100 cm H2O (73.7 mm Hg) or more (108 patients) were treated by anal dilatation (37), sphincterotomy (34), or high-fibre diet (37). Four and 12 months later anal dilatation had produced significantly better results than sphincterotomy or diet. Furthermore, anal dilatation was the only treatment associated with a significant reduction in anal pressure at four and 12 months. Patients with pressures under 100 cm H2O (108 patients) were treated by rubber-band ligation (35), cryosurgery (36), or diet (37). Four and 12 months later significantly more patients were improved by rubber-band ligation than by cryosurgery or diet. These results suggest that haemorrhoids in patients with excessive activity of the internal anal sphincter are best treated by anal dilatation and that in all other patients rubber-band ligation is the treatment of choice.